Measurement of CP asymmetry in B0s → D∓sK± decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
A measurement of the CP-violating parameters in B0s → D∓s K± decays is reported, based on the analysis of proton-proton collision data collected by the LHCb experiment corresponding to an integrated luminosity of 6 fb−1 at a centre-of-mass energy of 13 TeV. The measured parameters are obtained with a decay-time dependent analysis yielding Cf = 0.791 ± 0.061 ± 0.022, ADelta Gammaf = −0.051 ± 0.134 ± 0.058, A Delta Gamma f = −0.303 ± 0.125 ± 0.055, Sf = −0.571 ± 0.084 ± 0.023 and Sf= −0.503 ± 0.084 ± 0.025, where the first uncertainty is statistical and the second systematic. This corresponds to CP violation in the interference between mixing and decay of about 8.6 σ. Together with the value of the B0s mixing phase −2βs, these parameters are used to obtain a measurement of the CKM angle γ equal to (74 ± 12)° modulo 180°, where the uncertainty contains both statistical and systematic contributions. This result is combined with the previous LHCb measurement in this channel using 3 fb−1 resulting in a determination of gamma =(81+12-11)circ.
Im Titel sind die Zahl "0" sowie die Plus- und Minuszeichen hochgestellt
Im Titel ist der Buchstabe "s" jeweils tiefgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascón, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M.D Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 15.10.2025